2018
DOI: 10.1016/j.nano.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biodistribution and toxicology studies of cadmium-free indium-based quantum dot nanoparticles in a rat model

Abstract: Quantum dot (QD) nanoparticles are highly promising contrast agents and probes for biomedical applications owing to their excellent photophysical properties. However, toxicity concerns about commonly used cadmium-based QDs hinder their translation to clinical applications. In this study we describe the in vivo biodistribution and toxicology of indium-based water soluble QDs in rats following intravenous administration. The biodistribution measured at up to 90 days showed that QDs mainly accumulated in the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Quantum dots (QDs) with a diameter of 1-10 nm, have unique optical properties, such as broad excitation, narrow emission spectra, and long fluorescence lifetimes (Yaghini et al, 2018;Lu et al, 2019;Touaylia and Labiadh, 2019). These advantages make QDs attractive for biomedical applications, including fluorescent probes, clinical diagnostic, and therapeutic tools (Yaghini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum dots (QDs) with a diameter of 1-10 nm, have unique optical properties, such as broad excitation, narrow emission spectra, and long fluorescence lifetimes (Yaghini et al, 2018;Lu et al, 2019;Touaylia and Labiadh, 2019). These advantages make QDs attractive for biomedical applications, including fluorescent probes, clinical diagnostic, and therapeutic tools (Yaghini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Quantum dots (QDs) with a diameter of 1-10 nm, have unique optical properties, such as broad excitation, narrow emission spectra, and long fluorescence lifetimes (Yaghini et al, 2018;Lu et al, 2019;Touaylia and Labiadh, 2019). These advantages make QDs attractive for biomedical applications, including fluorescent probes, clinical diagnostic, and therapeutic tools (Yaghini et al, 2018). Commercially available cadmium-based QDs release toxic cadmium ions, which limit their future applicability, particularly in view of environmental regulations (Sudhagar et al, 2011;Aboulaich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yaghini et al found that InP QDs mainly accumulated in the liver and spleen of rats, with no obvious organ damage, histopathological lesions or serum biochemical changes when the rats were injected intravenously with InP QDs at the dose of 12.5mg/kg body weight (BW) or 50mg/kg BW. 19 Brunetti et al found that the toxicity of InP/ZnS QDs was much lower than that of CdSe/ZnS QDs by comparing their toxicity in vitro and in vivo (animal model Drosophila), and they considered InP/ZnS QDs were safer alternatives to CdSe/ZnS QDs. 20 However, some published studies have provided evidence of biological damage caused by InP QDs.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Cadmium-free QDs have been developed, including indium-based QDs, to alleviate these concerns and render the QDs biocompatible. [24][25][26] Herein, we present novel light-activated polyurethane surfaces embedded with indium-based cadmium-free quantum dots and crystal violet dye and evaluate their antibacterial effectiveness against environmental and clinical isolates of Gram-negative E. coli and P. aeruginiosa pathogens. E. coli and P. aeruginosa colonise hospital water environments and there is opportunity for genetic exchange between them (with the potential for exchange of antibiotic resistance genes and virulence factors).…”
Section: Introductionmentioning
confidence: 99%